Electrodeposition and Characteristics of Highly Ordered Macroporous Î²-PbO2 Electrodes - Mohd, Yusairie (Journal of Science and Technology, 2011)
Highly ordered macroporous β-PbO2 deposits were successfully produced on gold using polystyrene microsphere templates through electrodeposition technique from acidic nitrate baths containing Pb(II) ions using a constant current at 298 K. The morphology, catalytic activity and chemical stability of the deposits have been investigated. The morphology of the deposits has been analysed by Scanning Electron Microscopy (SEM). The catalytic activity of the deposited β-PbO2 electrodes as anodes for dimethylsulfoxide (DMSO) oxidation has been investigated using cyclic voltammetry. The chemical stability of the electrode in acidic solution was monitored and observed by the SEM. The deposits were shown to be active for the oxidation of DMSO due to their high surface area. It was also found that decomposition of the electrodes occurred when they were kept standing in acidic solution containing an oxidisable organic compound (ie: DMSO) on open circuit.